KONSTRUKSI MAKNA SAKIT BAGI PENGGUNA HALODOC - Asri Fitrananda, Charisma (Linimasa : Jurnal Ilmu Komunikasi, 2022)
The healthcare services have become a means for the community to support their healthcare needs. In Indonesia, there are several healthcare service units that can be directly accessed by the public, ranging from clinics, community health centers, and hospitals. Generally, these healthcare services are divided into a hierarchy or level of healthcare services. Halodoc is a telemedicine-based communication media used for health purposes by consulting remotely with doctors. This allows for interpersonal communication processes between doctors and patients without face-to-face or direct meetings. This consultation is more known as a mediated interpersonal communication process, where communication between individuals uses media as a means of communication. This qualitative research uses the phenomenology approach of Alfred Schutz, which focuses on exploring the subjective experiences of humans to understand and explore how humans give meaning to the world around them. There are ten informants divided into three categories, with the primary informants being ten students in the Greater Bandung area who use the Halodoc application. The findings show that: 1) the students' motives for continuing to use the Halodoc application after the pandemic are because Halodoc is still a practical, effective, efficient, accessible healthcare platform that can meet their other healthcare needs; 2) the actions taken by students are based on their motives, such as choosing Halodoc features like chatting with doctors, the pharmacy, and cashless payment; and 3) the students' construction of the meaning of "illness" is that they interpret it as a time to